The physical geography of the Mediterranean - Woodward, Jamie C. (Oxford regional environments., 2009)
This volume explores the climates, landscapes, ecosystems and hazards that comprise the Mediterranean world. It traces the development of the Mediterranean landscape over very long timescales and examines modern processes and key environmental issues in a wide range of settings. The Mediterranean is the only region on Earth where three continents meet and this interaction has produced a very distinctive Physical Geography. This book examines the landscapes and processes at themargins of these continents and the distinctive marine environment between them. Catastrophic earthquakes, explosive vo.